Odpowiedzi

2009-12-09T17:53:58+01:00
Metoda podstawiania

2x+3y=0.5
3x+y= -1

y=-1 -3x
2x+3(-1-3x)=0,5

y=-1-3x
2x-3-9x=0,5

y=-1-3x
-7x=3,5 / (-7)

x=-0,5
y=-1-1,5=-2,5

Metoda przeciwnych współczynników

2x+3y=0.5
3x+y= -1 /(-3)

2x+3y=0,5
-9x-3y=3 +
--------------
-7x=3,5 /(-7)
x=-0,5

x=-0,5
1,5+y= -1

x=-0,5
y=-2,5

Metoda podstawiania
b) 2x+y=14
8x+ 0,5y=35

y=14-2x
8x+7-x=35

y=14-2x
7x=28 /7

x=4
y=6

Metoda przeciwnych współczynników

2x+y=14
8x+ 0,5y=35

2x+y=14 / (-4)
8x+ 0,5y=35

-8x-4y=-56
8x+ 0,5y=35 +
----------------
-3,5y=-21 /(-3,5)
y=6

y=6
2x+6=14

y=6
x=4

Metoda przeciwnych współczynników
3x+4y=2
5x+7y=1

3x+4y=2 /5
5x+7y=1 /(-3)

15x+20y=10
-15x-21y=-3 +
-----------------
-y=7 / (-1)
y=-7

y=-7
3x-28=2

y=-7
x=10



  • Użytkownik Zadane
2009-12-09T17:54:10+01:00
A) (2x+3y=0,5
(3x+y=-1/*(-3)

(2x+3y=0,5
(-9x-3y=3
-7x=3,5/:(-7)
x=0,5

1.5+y=-1/-1,5
(y=-2,5
(x=0,5

b) (2x+y=14 /*1/2
(8x+1/2y=35

(-x-1/2y=-7
(8x+1/2y=35
7x=28/:7
x=4
8+y=14/-8
(y=6
(x=4
c) (3x+4y=2/ *(-5)
(5x+7y=1 / *3

( -15x-20y=-10
(15x+21y=3
y=-7

3x-28=2/+28
3x=30/:3
(x=10
(y=-7